Solid electrolyte composition and method for producing same

The active substance and solid electrolyte are combined by dry-thick kneading method to form a powder or clay solid electrolyte composition, which solves the problem of increasing resistance of wet battery and improves the discharge capacity and charge and discharge characteristics of the battery.

CN119174018APending Publication Date: 2024-12-20PANASONIC HOLDINGS CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380039971.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-03-02
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the prior art, there is a problem that the resistance increases when the battery is manufactured by wet method, resulting in a decrease in discharge capacity.

Method used

By adopting a dry thick kneading method including solvent, active substance and solid electrolyte, a powder or clay solid electrolyte composition is formed by combining the active substance with the solid electrolyte, thereby reducing the resistance of the battery and increasing the discharge capacity.

Benefits of technology

Effectively reduce the battery's resistance, improve the charge and discharge characteristics, increase the discharge capacity of the battery, and improve the ion and electron conductivity without the binder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174018A_ABST
    Figure CN119174018A_ABST
Patent Text Reader

Abstract

This solid electrolyte composition (1000) is provided with a solvent (120), an active material (110), and a solid electrolyte (100), the solid electrolyte composition (1000) being in the form of a powder or a clay, and the active material (100) and the solid electrolyte (100) being compounded. The solid content ratio of the solid electrolyte composition (1000) is, for example, 72% by mass or more and 88% by mass or less. A slurry for an electrode can be obtained by adding a solvent to the solid electrolyte composition (1000). An electrode and a battery may be fabricated using the electrode slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to solid electrolyte compositions and methods of making the same. Background Art

[0002] As a method for manufacturing a battery electrode, a dry method and a wet method are known. The wet method is a method using a slurry containing materials such as a solvent, an active material, and a solid electrolyte. The dry method is a method that does not use a solvent. Patent documents 1 and 2 disclose a method for manufacturing an electrode of an all-solid-state battery using a slurry.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2020 / 241322

[0006] Patent Document 2: Japanese Patent Application Publication No. 2020-53307 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In the prior art, it is desirable to increase the discharge capacity of a battery.

[0009] Means used to solve problems

[0010] The present disclosure provides a solid electrolyte composition, which comprises:

[0011] Solvents,

[0012] Active substances, and

[0013] Solid electrolytes,

[0014] The solid electrolyte composition is in powder or clay form.

[0015] The active material is composited with the solid electrolyte.

[0016] Effects of the Invention

[0017] According to the solid electrolyte composition of the present disclosure, the discharge capacity of the battery can be increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a cross-sectional view showing a schematic configuration of a solid electrolyte composition according to Embodiment 1.

[0019] Figure 2 It is a process diagram showing a method for producing a solid electrolyte composition.

[0020] Figure 3It is a process diagram showing a method for producing a slurry using a solid electrolyte composition.

[0021] Figure 4 This is a cross-sectional view showing a schematic structure of a battery according to the second embodiment.

[0022] Figure 5A is a SEM image of NCM before dry-mixing.

[0023] Figure 5B It is the SEM image of the composite of NCM and LYBC after dry mixing. DETAILED DESCRIPTION

[0024] (Understanding that forms the basis of the present disclosure)

[0025] The wet method is advantageous in that it can suppress the variation in electrode characteristics. However, although the reason is not necessarily clear, the wet method tends to increase the resistance of the battery. The increase in battery resistance leads to a decrease in discharge capacity.

[0026] The present inventors have conducted intensive research on a technique for reducing the resistance of a battery and increasing the discharge capacity, and have found that the discharge capacity of a battery can be increased by dry-mixing a mixture containing a solvent, an active material, and a solid electrolyte.

[0027] (Overview of one aspect of the present disclosure)

[0028] The solid electrolyte composition according to the first aspect of the present disclosure comprises:

[0029] Solvents,

[0030] Active substances, and

[0031] Solid electrolytes,

[0032] The solid electrolyte composition is in a powdery or clay form, and the active material is composited with the solid electrolyte.

[0033] According to the solid electrolyte composition disclosed herein, the discharge capacity of the battery can be increased. In addition, since the active material and the solid electrolyte are composited, the resistance of the battery can be effectively reduced.

[0034] In the second aspect of the present disclosure, for example, in the solid electrolyte composition according to the first aspect, the solid electrolyte composition may be in a clay state. When the solid electrolyte composition is in a clay state, the above-mentioned effects can be more fully obtained.

[0035] In the third aspect of the present disclosure, for example, the solid electrolyte composition according to the first or second aspect may have a solid content ratio of 72 mass % or more and 88 mass % or less. When the solid content ratio falls within this range, the above effects can be more fully obtained.

[0036] In the fourth aspect of the present disclosure, for example, the solid electrolyte composition according to any one of the first to third aspects may not contain a binder. When the solid electrolyte composition does not contain a binder, improvement in the ion conductivity of the electrode and improvement in the electronic conductivity in the electrode can be expected.

[0037] The method for producing a solid electrolyte composition according to the fifth embodiment of the present disclosure includes the following steps:

[0038] The mixture including the solvent, the active material and the solid electrolyte is dry-mixed.

[0039] According to the production method disclosed in the present invention, the active material and the solid electrolyte can be efficiently composited.

[0040] In the sixth aspect of the present disclosure, for example, according to the method for producing a solid electrolyte composition of the fifth aspect, the mixture may be in a clay state. If the mixture is in a clay state, dry-mixing can be performed using a kneader, planetary mixer, or the like, thereby efficiently advancing the composite formation of the active material and the solid electrolyte.

[0041] In the seventh aspect of the present disclosure, for example, according to the method for producing a solid electrolyte composition of the fifth or sixth aspect, the solid content ratio of the mixture may be 72 mass % or more and 88 mass % or less.

[0042] In the eighth aspect of the present disclosure, for example, according to the method for producing a solid electrolyte composition of the fifth or sixth aspect, the solid content ratio of the mixture may be 77% by mass or more and 84% by mass or less. If the solid content ratio is appropriately adjusted, the mixture can be kneaded easily and sufficiently.

[0043] In the ninth aspect of the present disclosure, for example, according to the method for producing a solid electrolyte composition according to any one of the fifth to eighth aspects, the mixture may not contain a binder. If the solid content ratio is appropriately adjusted, the mixture can be kneaded easily and sufficiently.

[0044] In a tenth aspect of the present disclosure, for example, according to the method for producing a solid electrolyte composition according to any one of the fifth to ninth aspects, the solid electrolyte may include at least one selected from the group consisting of sulfide solid electrolytes and halide solid electrolytes.

[0045] The method for producing an electrode slurry according to the eleventh aspect of the present disclosure includes the following steps:

[0046] A solvent is added to the solid electrolyte composition according to any one of the first to fourth aspects.

[0047] The method for manufacturing an electrode according to the twelfth aspect of the present disclosure includes the following steps:

[0048] The solid electrolyte composition according to any one of the first to fourth aspects is molded.

[0049] The manufacturing method of the battery according to the 13th aspect of the present disclosure includes the following steps:

[0050] The solid electrolyte composition according to any one of the first to fourth aspects is molded.

[0051] According to the eleventh to thirteenth aspects, the resistance of the battery can be further reduced, and the charge and discharge characteristics can be improved.

[0052] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0053] (Implementation Method 1)

[0054] Figure 1 1 is a cross-sectional view showing a schematic configuration of a solid electrolyte composition 1000 according to Embodiment 1. The solid electrolyte composition 1000 includes a solid electrolyte 100, an active material 110, and a solvent 120. The solid electrolyte composition 1000 is a solid component in a powdery or clay-like state.

[0055] The solid electrolyte composition 1000 is obtained by dry-mixing a mixture including a solvent 120, an active material 110, and a solid electrolyte 100. Through dry-mixing, a good interface is formed between the active material 110 and the solid electrolyte 100. As a result, the actual reaction area is increased and the resistance of the battery is reduced. As a result, the discharge capacity of the battery can be increased.

[0056] The solid electrolyte composition 1000 is preferably in a clay state. When the solid electrolyte composition 1000 is in a clay state, the above-mentioned effects can be more fully obtained. The solid electrolyte composition 1000 does not have fluidity like a slurry, but has a fixed shape.

[0057] In the solid electrolyte composition 1000, the active material 110 is composited with the solid electrolyte 100. With this configuration, the resistance of the battery can be effectively reduced, and as a result, the discharge capacity of the battery can be increased.

[0058] “The active material 110 and the solid electrolyte 100 are composited” means that the solid electrolyte 100 is attached to the active material 110 so as to cover at least a part of the surface of the particulate active material 110 .

[0059] The solvent 120 adheres to the surface of the complex of the active material 110 and the solid electrolyte 100 .

[0060] The solid content ratio of the solid electrolyte composition 1000 may be 72% by mass or more and 88% by mass or less. When the solid content ratio falls within this range, the above-mentioned effects can be more fully obtained. The solid content ratio of the solid electrolyte composition 1000 may be 77% by mass or more and 84% by mass or less.

[0061] The solid electrolyte composition 1000 may not contain a binder. When the solid electrolyte composition 1000 does not contain a binder, it is expected that the ion conductivity of the electrode and the electron conductivity in the electrode will be improved.

[0062] The solid electrolyte composition 1000 may include a conductive aid 130. The conductive aid 130 helps to form an electron conduction path inside the battery.

[0063] A material that can be used as an active material of a lithium ion secondary battery can be used as the active material 110. The active material 110 is, for example, a positive electrode active material.

[0064] Examples of positive electrode active materials include LiCoO2, LiNi x Me 1-x O2 (0.5≤x<1, Me contains at least one selected from the group consisting of Co, Mn and Al), LiNi x Co 1-x O2(0 <x<0.5)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMnO2, heterogeneous element substituted Li-Mn spinel, lithium titanate, lithium metal phosphate, transition metal oxides, etc. Examples of heterogeneous element substituted Li-Mn spinel include LiMn 1.5 Ni 0.5 O4、LiMn 1.5 Al 0.5 O4、LiMn 1.5 Mg 0.5 O4、LiMn 1.5 Co 0.5 O4、LiMn 1.5 Fe 0.5 O4、LiMn 1.5 Zn 0.5 O4, etc. As lithium titanate, Li4Ti5O 12As lithium metal phosphate, LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, etc. are listed. As transition metal oxide, V2O5, MoO3, etc. are listed.

[0065] Among the above materials, LiCoO2, LiNi x Me 1-x O2 (0.5≤x<1, Me contains at least one selected from the group consisting of Co, Mn and Al), LiNi x Co 1-x O2(0 <x<0.5)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The lithium-containing composite oxides include O2, LiMnO2, heterogeneous element substituted Li-Mn spinel, lithium metal phosphate, etc. More preferably, the lithium-containing composite oxides have a layered rock salt structure.

[0066] The active material 110 may be a negative electrode active material. Examples of the negative electrode active material include metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, and the like. The metal material may be a single metal or an alloy. Examples of the metal material include lithium metal and lithium alloys. Examples of the carbon material include natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite, and amorphous carbon. From the perspective of capacity density, silicon (Si), tin (Sn), silicon compounds, or tin compounds may be suitably used.

[0067] The active material 110 has a particle shape, for example. The shape of the particles of the active material 110 is not particularly limited. The shape of the particles of the active material 110 may be spherical, ellipsoidal, scaly, or fibrous.

[0068] The active material 110 may be covered by the covering material 140. The covering material 140 may cover the entire surface of the active material 110 or may cover the surface of the active material 110 partially.

[0069] The coating material 140 may include Li and at least one element selected from the group consisting of O, F, and Cl.

[0070] The coating material 140 may include at least one selected from the group consisting of lithium niobate, lithium phosphate, lithium titanate, lithium tungstate, lithium zirconate fluoride, lithium aluminate fluoride, lithium titanate fluoride, and lithium magnesium fluoride.

[0071] The solid electrolyte 100 may include at least one selected from the group consisting of a sulfide solid electrolyte and a halide solid electrolyte. According to the above configuration, the output characteristics of the battery can be improved. A sulfide solid electrolyte is a solid electrolyte containing sulfur. A halide solid electrolyte is a solid electrolyte containing halogen.

[0072] The solid electrolyte 100 may be a mixture of a sulfide solid electrolyte and a halide solid electrolyte.

[0073] As sulfide solid electrolytes, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 In addition, sulfide solid electrolytes with an argyrodite structure represented by Li6PS5Cl, Li6PS5Br, Li6PS5I, etc. can be used. LiX, Li2O, MO q , Li p MO q etc. Here, X is at least one selected from the group consisting of F, Cl, Br and I. In addition, M is at least one selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe and Zn. p and q are natural numbers. One or more sulfide solid electrolytes selected from the above materials can be used.

[0074] According to the above configuration, the ion conductivity of the sulfide solid electrolyte can be further improved, thereby further improving the charge and discharge efficiency of the battery.

[0075] The halide solid electrolyte is represented by, for example, the following composition formula (1).

[0076] Li α M β X γ …Formula (1)

[0077] Here, α, β, and γ are each independently a value greater than 0. M includes at least one element selected from the group consisting of metal elements and semi-metal elements other than Li. X includes at least one element selected from the group consisting of F, Cl, Br, and I.

[0078] In the present disclosure, "semi-metallic elements" refer to B, Si, Ge, As, Sb, and Te. "Metallic elements" refer to all elements included in Groups 1 to 12 of the periodic table except hydrogen, and all elements included in Groups 13 to 16 of the periodic table except B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se. That is, "semi-metallic elements" or "metallic elements" refer to an element group that can become a cation when forming an inorganic compound with a halogen element.

[0079] The halide solid electrolyte represented by the composition formula (1) has a higher ion conductivity than a halide solid electrolyte such as LiI formed by Li and a halogen element. Therefore, according to the halide solid electrolyte represented by the composition formula (1), the ion conductivity of the halide solid electrolyte can be further improved.

[0080] In the composition formula (1), M may be at least one element selected from the group consisting of metal elements other than Li and semi-metal elements.

[0081] In the composition formula (1), X may be at least one selected from the group consisting of F, Cl, Br and I.

[0082] The composition formula (1) may satisfy 2.5≤α≤3, 1≤β≤1.1, and γ = 6. According to the above configuration, the ion conductivity of the halide solid electrolyte can be further improved.

[0083] In the composition formula (1), M may include Y (=yttrium). That is, the halide solid electrolyte may include Y as a metal element. According to the above configuration, the ion conductivity of the halide solid electrolyte can be further improved.

[0084] The halide solid electrolyte containing Y may be, for example, Li a Me b Y c A compound represented by the composition formula of X6. Here, a+mb+3c=6 and c>0 are satisfied. Me is at least one element selected from the group consisting of metal elements and semi-metal elements other than Li and Y. M is the valence of the element Me. X is at least one element selected from the group consisting of F, Cl, Br and I.

[0085] Me may be, for example, at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb.

[0086] According to the above configuration, the ion conductivity of the halide solid electrolyte can be further improved.

[0087] As the halide solid electrolyte, for example, the following materials can be used. According to the following configuration, the ion conductivity of the halide solid electrolyte can be further improved.

[0088] The halide solid electrolyte may be a material represented by the following composition formula (A1).

[0089] Li 6-3d Y d X6…Formula (A1)

[0090] In composition formula (A1), X is at least one selected from the group consisting of F, Cl, Br and I. In addition, <d<2。

[0091] The halide solid electrolyte may be a material represented by the following composition formula (A2).

[0092] Li3YX6…Formula (A2)

[0093] In composition formula (A2), X is at least one selected from the group consisting of F, Cl, Br and I.

[0094] The halide solid electrolyte may be a material represented by the following composition formula (A3).

[0095] Li 3-3δ Y 1+δ Cl6…Formula (A3)

[0096] In composition formula (A3), 0<δ≤0.15 is satisfied.

[0097] The halide solid electrolyte may be a material represented by the following composition formula (A4).

[0098] Li 3-3δ Y 1+δ Br6…Formula (A4)

[0099] In composition formula (A4), 0<δ≤0.25 is satisfied.

[0100] The halide solid electrolyte may be a material represented by the following composition formula (A5).

[0101] Li 3-3δ+a Y 1+δ-a Me a Cl 6-x-y Br x I y …Formula (A5)

[0102] In composition formula (A5), Me includes at least one selected from the group consisting of Mg, Ca, Sr, Ba, and Zn. Me may be at least one selected from the group consisting of Mg, Ca, Sr, Ba, and Zn.

[0103] In the compositional formula (A5), -1 < δ < 2, 0 < a < 3, 0 < (3 - 3δ + a), 0 < (1 + δ - a), 0 ≤ x ≤ 6, 0 ≤ y ≤ 6, and (x + y) ≤ 6 are satisfied.

[0104] The halide solid electrolyte can be a material represented by the following compositional formula (A6).

[0105] Li 3-3δ Y 1+δ-a Me a Cl 6-x-y Br x I y … Formula (A6)

[0106] In the compositional formula (A6), Me includes at least one selected from the group consisting of Al, Sc, Ga, and Bi. Me can be at least one selected from the group consisting of Al, Sc, Ga, and Bi.

[0107] In the compositional formula (A6), -1 < δ < 1, 0 < a < 2, 0 < (1 + δ - a), 0 ≤ x ≤ 6, 0 ≤ y ≤ 6, and (x + y) ≤ 6 are satisfied.

[0108] The halide solid electrolyte can be a material represented by the following compositional formula (A7).

[0109] Li 3-3δ-a Y 1+δ-a Me a Cl 6-x-y Br x I y … Formula (A7)

[0110] In the compositional formula (A7), Me includes at least one selected from the group consisting of Zr, Hf, and Ti. Me can be at least one selected from the group consisting of Zr, Hf, and Ti.

[0111] In the compositional formula (A7), -1 < δ < 1, 0 < a < 1.5, 0 < (3 - 3δ - a), 0 < (1 + δ - a), 0 ≤ x ≤ 6, 0 ≤ y ≤ 6, and (x + y) ≤ 6 are satisfied.

[0112] The halide solid electrolyte can be a material represented by the following compositional formula (A8).

[0113] Li 3-3δ-2a Y 1+δ-a Me a Cl 6-x-y Br x I y … Formula (A8)

[0114] In the compositional formula (A8), Me includes at least one selected from the group consisting of Ta and Nb. Me may be at least one selected from the group consisting of Ta and Nb.

[0115] In the compositional formula (A8), -1 < δ < 1, 0 < a < 1.2, 0 < (3 - 3δ - 2a), 0 < (1 + δ - a), 0 ≤ x ≤ 6, 0 ≤ y ≤ 6, and (x + y) ≤ 6 are satisfied.

[0116] As the halide solid electrolyte, more specifically, for example, Li3YX6, Li2MgX4, Li2FeX4, Li(Al, Ga, In)X4, Li3(Al, Ga, In)X6, etc. can be used. Here, X is at least one selected from the group consisting of F, Cl, Br, and I.

[0117] In the present disclosure, the expression “(A, B, C)” in the chemical formula means “at least one selected from the group consisting of A, B, and C”. For example, “(Al, Ga, In)” is synonymous with “at least one selected from the group consisting of Al, Ga, and In”. The same applies to other elements.

[0118] The halide solid electrolyte may not contain sulfur. According to the above configuration, the generation of hydrogen sulfide gas can be suppressed. Therefore, a battery with improved safety can be achieved.

[0119] The halide solid electrolyte may be an oxygen-containing oxohalide-based solid electrolyte.

[0120] The shape of the solid electrolyte 100 is not particularly limited. The shape of the solid electrolyte 100 can be, for example, needle-like, spherical, ellipsoidal, etc. For example, the shape of the solid electrolyte 100 can be granular.

[0121] For example, when the shape of the solid electrolyte 100 is granular (e.g., spherical), the median particle size of the solid electrolyte 100 can be 100 μm or less. When the median particle size of the solid electrolyte 100 is 100 μm or less, the active material 110 and the solid electrolyte 100 in the solid electrolyte composition 1000 can form a good composite state. Thereby, the charge and discharge characteristics of the battery are improved.

[0122] The median particle size of the solid electrolyte 100 can be 10 μm or less. According to the above configuration, the active material 110 and the solid electrolyte 100 in the solid electrolyte composition 1000 can form a good composite state.

[0123] The median particle size of the solid electrolyte 100 can be smaller than the median particle size of the active material 110. According to the above configuration, better composite formation between the active material 110 and the solid electrolyte 100 can be achieved in the solid electrolyte composition 1000.

[0124] The solvent 120 can be selected according to the reactivity to the active material 110, the reactivity to the solid electrolyte 100, the adsorption to these materials, etc. The solvent 120 is not particularly limited as long as it does not react with the solid electrolyte and cause a significant decrease in ion conductivity. As a solvent 120 suitable for a halide solid electrolyte, tetralin, ethylbenzene, mesitylene, unimellitic toluene, xylene, isopropylbenzene, 1,2,4-trichlorobenzene, chlorobenzene, 2,4-dichlorobenzene, o-chlorotoluene, 1,3-dichlorobenzene, p-chlorotoluene, 1,2-dichlorobenzene, 1,4-dichlorobutane, 3,4-dichlorotoluene, pentane, etc. can be listed. A mixture of one or more selected from them can be used as the solvent 120. As a solvent 120 suitable for a sulfide solid electrolyte, tetralin, anisole, xylene, octane, hexane, decalin, butyl acetate, ethyl propionate, tripropylamine, etc. can be listed. One or a mixture of two or more selected from these may be used as the solvent 120. The solvent 120 may be selected according to the types of the conductive auxiliary agent and the binder.

[0125] Examples of the conductive additive 130 include graphites such as natural graphite or artificial graphite, carbon blacks such as acetylene black, furnace black, and Ketjen black, conductive fibers such as carbon fibers and metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene, etc. When a carbon conductive additive is used, low cost can be achieved.

[0126] According to the above configuration, the resistance of the battery can be further reduced, and the charge and discharge characteristics can be improved.

[0127] Next, a method for producing the solid electrolyte composition 1000 will be described. Figure 2 1 is a process diagram showing a method for producing the solid electrolyte composition 1000 .

[0128] The pre-treatment process of step S1 is a process for crushing and breaking the solid electrolyte 100 to control the particle diameter, or for dispersing the solid electrolyte 100 in a solvent to inhibit aggregation. In the pre-treatment process, in order to improve the efficiency of crushing and breaking, a dispersant and / or a binder can be used. By carrying out the pre-treatment process, the efficiency of the dry thick mixing process and the efficiency of the manufacture of the battery can be achieved. However, the pre-treatment process can be omitted.

[0129] The active material 110 may be subjected to a pretreatment step.

[0130] In step S2, a dry-mix kneading step is performed. The dry-mix kneading step is a step of kneading a solid component in a powdery to clay-like state, which is a mixture of a solid and a liquid.

[0131] In the dry-mixing process, first, the active material 110, the solid electrolyte 100 and the solvent 120 are mixed to prepare a mixture. Then, the mixture is dry-mixed. Thus, the composite of the active material 110 and the solid electrolyte 100 is efficiently promoted. As the active material 110, a single material can be used, or a combination of multiple materials can be used. As the solid electrolyte 100, a single material can be used, or a combination of multiple materials can be used. As the solvent 120, a single material can be used, or a combination of multiple materials can be used.

[0132] In the above mixture, the mass ratio of the active material 110 to the solid electrolyte 100 is not particularly limited. For example, the mass ratio of the active material 110 to the solid electrolyte 100 can be adjusted within the range of (active material):(solid electrolyte)=99.5:0.5 to 60:40.

[0133] In order to efficiently promote the composite of the active material 110 and the solid electrolyte 100, the solid content ratio of the mixture is, for example, 72% by mass or more and 88% by mass or less, and can be 77% by mass or more and 84% by mass or less. If the solid content ratio is properly adjusted, the mixture can be easily and fully mixed. That is, since the mixture does not have fluidity such as a slurry and has a moderate viscosity, it is easy to apply shear force to the mixture during dry thick mixing. As a result, dry thick mixing can be efficiently implemented. It is also easy to uniformly perform the composite of the active material 110 and the solid electrolyte 100.

[0134] In one example, the mixture to be subjected to dry-mixing is in a clay state. If the mixture is in a clay state, dry-mixing can be performed using a kneader, a planetary mixer, or the like, and the active material 110 and the solid electrolyte 100 can be efficiently composited.

[0135] The processing time in the dry-mixing process is not particularly limited. The processing time can be appropriately adjusted in the range of 30 minutes to several hours, for example. In order to avoid the reaction of the solid electrolyte 100 with moisture in the air, it is ideal to carry out the dry-mixing process in an inactive atmosphere with a low dew point. For example, the dry-mixing process can be carried out in an argon atmosphere or a dry air atmosphere with a dew point below -60°C. In the case where the temperature of the mixture rises due to friction, the dry-mixing process can be carried out while cooling the mixture.

[0136] The mixture provided for dry mixing may not contain a binder. If a binder is included, the liquid retention of the mixture and the viscosity of the solid electrolyte composition increase, so the dry mixing process can be efficiently implemented. However, if the binder covers the surface of the active material 110 and the solid electrolyte 100, the binder will constitute the main cause of hindering electronic conductivity and lithium ion conductivity. In the absence of a binder, it can be expected that electronic conductivity and lithium ion conductivity will be improved.

[0137] The content of the polymer material functioning as a binder in the mixture subjected to dry-mixing may be 0.1% by mass or less. Similarly, the content of the polymer material functioning as a binder in the solid electrolyte composition 1000 obtained by dry-mixing may be 0.1% by mass or less.

[0138] As the solid electrolyte 100, at least one selected from the sulfide solid electrolyte and the halide solid electrolyte described above can be used. Since these solid electrolytes are relatively easily deformed, they are suitable for the manufacture of the solid electrolyte composition 1000 based on dry-mixed mixing. In the case where solid materials such as the active material 110 and the solid electrolyte 100 are easily deformed, the active material 110 and the solid electrolyte 100 can be efficiently composited based on dry-mixed mixing.

[0139] High torque devices such as kneaders and planetary mixers that can mix and knead materials with strong shear force are suitable for dry mixing. These devices can work at low speeds below 1000 rpm.

[0140] The mixture subjected to dry-mixing may contain a conductive additive. In addition, the conductive additive may be subjected to a pretreatment step similar to the solid electrolyte 100. In the pretreatment step, a dispersant and / or a binder may be used.

[0141] (Implementation Method 2)

[0142] Figure 3 1 is a process diagram showing a method for producing a slurry using the solid electrolyte composition 1000 .

[0143] The solid electrolyte composition 1000 lacks fluidity. It is difficult to directly apply the solid electrolyte composition 1000 to form a coating film. Therefore, a solvent is added to the solid electrolyte composition 1000 to prepare an electrode slurry. A binder, a dispersant, an additional solid electrolyte, an additional conductive additive, etc. may be mixed into the solid electrolyte composition 1000 as needed.

[0144] The pre-treatment process shown in step ST1 is a process for pulverizing and crushing various materials to control particle diameters, or for dispersing various materials in a solvent to suppress aggregation. The pre-treatment process may be omitted.

[0145] The mixing process shown in step ST2 is a process for mixing the solid electrolyte composition 1000 with an additional solvent. The mixing process can be a process for dispersing the solid electrolyte composition 1000 in an additional solvent. The additional solvent can be the same solvent as the solvent contained in the solid electrolyte composition 1000, or a solvent different from the solvent contained in the solid electrolyte composition 1000. Devices that can easily exert a dispersing effect on low-viscosity materials, such as devices that rotate at a high speed of more than 1000 rpm and devices that use ultrasonic waves, are suitable for the mixing process. However, a device that can implement both a dry-mixing process and a mixing process can be used to continuously implement a dry-mixing process for obtaining a solid electrolyte composition 1000 and a mixing process for preparing a slurry.

[0146] Through the above steps, an electrode slurry can be obtained. When the electrode slurry is used to produce an electrode and a battery, the resistance of the battery can be reduced and the charge and discharge characteristics of the battery can be improved.

[0147] (Implementation 3)

[0148] Figure 4 2 is a cross-sectional view showing a schematic configuration of a battery 2000 according to Embodiment 3. The battery 2000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0149] At least one of the positive electrode 201 and the negative electrode 203 can be produced by molding the solid electrolyte composition 1000. Specifically, at least one of the positive electrode 201 and the negative electrode 203 can be produced by applying an electrode slurry prepared using the solid electrolyte composition 1000 to a current collector to form a coating film and removing the solvent from the coating film. However, there is also a method of directly molding the solid electrolyte composition 1000 without passing through the electrode slurry.

[0150] At least one of the positive electrode 201 and the negative electrode 203 includes an active material 110 and a solid electrolyte 100. Optionally, at least one of the positive electrode 201 and the negative electrode 203 may include a binder, a dispersant, a conductive aid, and the like.

[0151] The battery 2000 is manufactured using the solid electrolyte composition 1000. Therefore, compared with a battery manufactured using a slurry prepared by mixing an active material, a solid electrolyte, and a solvent, it can have a higher discharge voltage and a higher discharge capacity.

[0152] Regarding the volume ratio "v1:100-v1" of the positive electrode active material and the solid electrolyte, 30≤v1≤95 may be satisfied. When 30≤v1 is satisfied, the energy density of the battery 2000 can be sufficiently ensured. In addition, when v1≤95 is satisfied, it is possible to operate at a high output power. At this time, the positive electrode active material may include an active material 110. The solid electrolyte may include a solid electrolyte 100.

[0153] The thickness of the positive electrode 201 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 is 10 μm or more, the energy density of the battery 2000 can be sufficiently ensured. When the thickness of the positive electrode 201 is 500 μm or less, the battery 2000 can operate at a high output.

[0154] The electrolyte layer 202 is a layer containing an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. That is, the electrolyte layer 202 may be a solid electrolyte layer. As the solid electrolyte, the material exemplified as the material of the solid electrolyte 100 in Embodiment 1 may be used. That is, the electrolyte layer 202 may contain a solid electrolyte having the same composition as the solid electrolyte 100 contained in the solid electrolyte composition 1000.

[0155] According to the above configuration, the charge and discharge efficiency of the battery 2000 can be further improved.

[0156] The electrolyte layer 202 may include a halide solid electrolyte having a composition different from that of the solid electrolyte included in the solid electrolyte composition 1000 .

[0157] The electrolyte layer 202 may include a sulfide solid electrolyte.

[0158] The electrolyte layer 202 may include only one solid electrolyte selected from the above-mentioned group of solid electrolytes, or may include two or more solid electrolytes selected from the above-mentioned group of solid electrolytes. The plurality of solid electrolytes have different compositions from each other. For example, the electrolyte layer 202 may include a halide solid electrolyte and a sulfide solid electrolyte.

[0159] The thickness of the electrolyte layer 202 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 202 is 1 μm or more, the positive electrode 201 and the negative electrode 203 are unlikely to short-circuit. When the thickness of the electrolyte layer 202 is 300 μm or less, high output power can be achieved.

[0160] The negative electrode 203 includes a material having the property of storing and releasing metal ions (for example, lithium ions). The negative electrode 203 includes, for example, a negative electrode active material. In this case, the negative electrode active material may include the active material 110.

[0161] The negative electrode 203 may include a solid electrolyte material. In this case, the negative electrode 203 may include a solid electrolyte 100. According to the above configuration, the lithium ion conductivity inside the negative electrode 203 is improved, and it can work at a high output power. As a solid electrolyte, the material exemplified in Embodiment 1 can be used. That is, the negative electrode 203 may include a solid electrolyte having the same composition as the solid electrolyte contained in the solid electrolyte composition 1000.

[0162] The median particle size of the negative electrode active material may be 0.1 μm or more and 100 μm or less.

[0163] When the median particle size of the negative electrode active material is 0.1 μm or more, the negative electrode active material and the solid electrolyte material can be well dispersed, thereby improving the charge and discharge characteristics of the battery.

[0164] Furthermore, when the median particle size of the negative electrode active material is 100 μm or less, the diffusion rate of lithium in the negative electrode active material can be sufficiently ensured, so that the battery can operate at a high output.

[0165] The median particle size of the negative electrode active material is larger than that of the solid electrolyte material, thereby achieving a good dispersion state of the negative electrode active material and the solid electrolyte material.

[0166] The volume ratio "v2:100-v2" of the negative electrode active material and the solid electrolyte material contained in the negative electrode 203 may satisfy 30≤v2≤95. When 30≤v2 is satisfied, the energy density of the battery 2000 can be sufficiently ensured. In addition, when v2≤95 is satisfied, the battery can operate at a high output power.

[0167] The thickness of the negative electrode 203 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 203 is 10 μm or more, the energy density of the battery 2000 can be sufficiently ensured. When the thickness of the negative electrode 203 is 500 μm or less, the battery 2000 can operate at a high output.

[0168] In at least one of the groups consisting of the positive electrode 201, the electrolyte layer 202 and the negative electrode 203, a binder may be included for the purpose of improving the adhesion between the particles. The binder is used to improve the adhesion of the material constituting the electrode. As a binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose, etc. can be listed. In addition, as a binder, a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, hexadiene can be used. In addition, two or more selected from them can be mixed and used as a binder.

[0169] At least one selected from the group consisting of the positive electrode 201 and the negative electrode 203 may contain a conductive aid for the purpose of improving electronic conductivity. In this case, the conductive aid may include a conductive aid 130. As the conductive aid, for example, graphites such as natural graphite or artificial graphite, carbon blacks such as acetylene black and Ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene, etc. can be used. When a carbon conductive aid is used, low cost can be achieved.

[0170] Examples of the shape of the battery 2000 include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, and a laminated shape.

[0171] Example

[0172] Hereinafter, the present disclosure will be described in more detail with reference to examples.

[0173] 《Example 1》

[0174] [Production of halide solid electrolyte]

[0175] In an argon glove box at a dew point below -60°C, LiBr, LiCl and YCl3 were weighed in a molar ratio of LiBr:LiCl:YCl3=2:1:1. They were crushed and mixed in a mortar to obtain a mixture. The mixture was ground using a planetary ball mill at 600 rpm for 12 hours. Thus, a powder of a halide solid electrolyte represented by the composition formula of Li3YBr2Cl4 was obtained. Hereinafter, Li3YBr2Cl4 will be referred to as "LYBC".

[0176] [Preparation of Solid Electrolyte Composition]

[0177] In an environment with a dew point of -60°C or less, LYBC powder and p-chlorotoluene (pCT) were mixed and pre-treated by finely pulverizing the LYBC powder using a planetary ball mill to obtain a suspension containing LYBC.

[0178] Li(NiCoMn)O2 (hereinafter referred to as "NCM") as a positive electrode active material and LYBC were placed in a kneader (PBV-0.1 manufactured by Irie Shokai Co., Ltd.) in a mass ratio of NCM:LYBC=93.0:7.0, and parachlorotoluene was added to adjust the solid content ratio to 80.9% by mass. Then, dry kneading was performed under the conditions of a rotation speed of 60 rpm, 1 hour, and an argon atmosphere with a dew point of -60°C. Thus, the solid electrolyte composition of Example 1 was obtained.

[0179] Figure 5A is a SEM image of NCM before dry-mixing. Figure 5B This is a SEM image of the composite of NCM and LYBC after dry-mixing. The composite was dried for SEM observation. Figure 5A As shown in FIG. 1 , the NCM before dry-mixing is a secondary particle with large concavities and convexities on the surface. Figure 5B As shown, in the composite after dry kneading, LYBC adheres to the surface of NCM particles, the unevenness is reduced, and NCM and LYBC are composited.

[0180] [Production of positive electrode]

[0181] In an argon glove box at a dew point below -60°C, a solid electrolyte composition is mixed with a suspension containing LYBC to obtain a mixture. The ratio of NCM to LYBC in the mixture is NCM:LYBC = 70:30 by volume. The mixture is treated with a homogenizer to disperse the NCM and LYBC. A binder (SEBS, N504 manufactured by Asahi Kasei Corporation), a solvent and a conductive aid (fibrous carbon, VGCF-H manufactured by Showa Denko K.K.) are added to the mixture and dispersed with a homogenizer to obtain a slurry. The solvent used in making the slurry is the same as the solvent contained in the solid electrolyte composition (parachlorotoluene). "VGCF" is a registered trademark of Showa Denko K.K.

[0182] The slurry is applied to a current collector to form a coating film, and the coating film is dried on a hot plate to prepare a positive electrode.

[0183] In Examples 1 to 11 and Comparative Example 21, the thickness of the coating film was adjusted in each of Examples and Comparative Example so that the mass of the positive electrode active material layer after drying would be the same.

[0184] [Production of sulfide solid electrolyte]

[0185] In an argon glove box with a dew point below -60°C, Li2S and P2S5 are weighed in a molar ratio of Li2S:P2S5=75:25. They are crushed and mixed in a mortar to obtain a mixture. Then, the mixture is ground using a planetary ball mill (P-7 model manufactured by Fritsch) at 510 rpm for 10 hours. Thus, a glassy solid electrolyte is obtained. The glassy solid electrolyte is heat treated in an inactive atmosphere at 270°C for 2 hours. Thus, Li2S-P2S5, a sulfide solid electrolyte in the form of a glass ceramic, is obtained. Hereinafter, Li2S-P2S5 will be referred to as "LPS".

[0186] [Battery production]

[0187] The positive electrode is cut into a disc shape. 80 mg of LPS and a disc-shaped positive electrode are stacked in order in an insulating outer cylinder. LPS and the positive electrode are press-formed at a pressure of 700 MPa. Metal Li (thickness 200 μm) is stacked on the opposite side of the positive electrode. The positive electrode, LPS and metal Li are press-formed at a pressure of 80 MPa to produce a stack consisting of a positive electrode, a solid electrolyte layer and a negative electrode. Stainless steel collectors are arranged above and below the stack. Collector leads are installed on each collector. The insulating outer cylinder is sealed by using an insulating ferrule to block the interior of the insulating outer cylinder from the external atmosphere. The battery of Example 1 is produced through the above process.

[0188] [Electrochemical test]

[0189] The battery was placed in a thermostatic chamber at 25°C and connected to a charge and discharge device. A constant current charge was performed to a voltage of 4.3V at a current value that reached a 0.05C rate (10-hour rate) relative to the theoretical capacity of the battery. Then, a constant current discharge was performed at a 0.3C rate to a voltage of 2.5V, and the average discharge voltage and discharge capacity per unit mass were measured. The discharge capacity per unit area at 0.3C (mWh / cm 2 ). The results are shown in Table 1. In Table 1, the item "discharge capacity" shows a relative value when the discharge capacity per unit area of ​​the battery of Comparative Example 1 is regarded as "100".

[0190] 《Example 2》

[0191] In an environment with a dew point below -60°C, LYBC powder is mixed with parachlorotoluene, and the LYBC powder is finely pulverized using a planetary ball mill to obtain a suspension. An appropriate amount of a conductive aid is added to the suspension and mixed using a stirrer. The amount of the conductive aid is adjusted so that the mass ratio of the conductive aid to the mass of LYBC is 5%. The amount of the conductive aid is also adjusted in the following examples and comparative examples.

[0192] NCM and the suspension were put into a kneader so that the mass ratio of NCM to LYBC was NCM:LYBC=93.0:7.0, and p-chlorotoluene was added to adjust the solid content ratio to 80.0% by mass. Dry kneading was carried out under the same conditions as in Example 1 to obtain a solid electrolyte composition of Example 2.

[0193] A battery of Example 2 was prepared by the same method as in Example 1 using the solid electrolyte composition of Example 2. An electrochemical test of the battery of Example 2 was carried out by the same method as in Example 1.

[0194] 《Example 3》

[0195] The solid electrolyte composition of Example 3 was prepared in the same manner as in Example 2 except that the mass ratio of NCM to LYBC was changed to NCM:LYBC=95.2:4.8 and the solid content ratio was changed to 83.0 mass %. The battery of Example 3 was prepared using the solid electrolyte composition of Example 3 in the same manner as in Example 1. The electrochemical test of the battery of Example 3 was carried out in the same manner as in Example 1.

[0196] 《Example 4》

[0197] The solid electrolyte composition of Example 4 was prepared in the same manner as in Example 2 except that the mass ratio of NCM to LYBC was changed to NCM:LYBC=90.9:9.1 and the solid content ratio was changed to 81.2% by mass. The battery of Example 4 was prepared using the solid electrolyte composition of Example 4 in the same manner as in Example 1. The electrochemical test of the battery of Example 4 was carried out in the same manner as in Example 1.

[0198] 《Example 5》

[0199] In an environment with a dew point of -60°C or less, LYBC powder is mixed with o-chlorotoluene (oCT), and the LYBC powder is finely pulverized using a planetary ball mill to obtain a suspension. An appropriate amount of a conductive additive is added to the suspension, and the mixture is mixed using a stirrer.

[0200] NCM and the suspension were put into a kneader so that the mass ratio of NCM to LYBC was NCM:LYBC=93.0:7.0, and o-chlorotoluene was added to adjust the solid content ratio to 81.8% by mass. Dry kneading was carried out under the same conditions as in Example 1 to obtain a solid electrolyte composition of Example 5.

[0201] Using the solid electrolyte composition of Example 5, a battery of Example 5 was produced in the same manner as in Example 1. Electrochemical tests of the battery of Example 5 were carried out in the same manner as in Example 1.

[0202] Example 6

[0203] [Preparation of coated positive electrode active material]

[0204] NCM is used as the positive electrode active material. LiNbO3 is used as the coating material. A coating layer containing LiNbO3 is formed by a liquid phase coating method. Specifically, first, lithium ethoxide, pentaethoxy niobium and super dehydrated ethanol are mixed to prepare a precursor solution of LiNbO3. Then, the precursor solution is applied to the surface of the NCM. Thus, a precursor film is formed on the surface of the NCM. Then, the NCM coated with the precursor film is heat-treated. The gelation of the precursor film is promoted by heat treatment to form a coating layer containing LiNbO3. Hereinafter, the NCM having a coating layer of LiNbO3 will be referred to as "NCM-Nb".

[0205] In an environment with a dew point of -60°C or less, LYBC powder is mixed with parachlorotoluene, and the LYBC powder is finely pulverized using a planetary ball mill to obtain a suspension. An appropriate amount of a conductive additive is added to the suspension, and the mixture is mixed using a stirrer.

[0206] NCM-Nb and the suspension were put into a kneader so that the mass ratio of NCM-Nb to LYBC was NCM-Nb:LYBC=93.0:7.0, and p-chlorotoluene was added to adjust the solid content ratio to 82.8% by mass. Dry kneading was carried out under the same conditions as in Example 1 to obtain a solid electrolyte composition of Example 6.

[0207] Using the solid electrolyte composition of Example 6, a battery of Example 6 was produced in the same manner as in Example 1. Electrochemical tests of the battery of Example 6 were carried out in the same manner as in Example 1.

[0208] Example 7

[0209] The solid electrolyte composition of Example 7 was prepared in the same manner as in Example 6 except that the mass ratio of NCM-Nb to LYBC was changed to NCM-Nb:LYBC=95.2:4.8 and the solid content ratio was changed to 83.0 mass %. The battery of Example 7 was prepared in the same manner as in Example 1 using the solid electrolyte composition of Example 7. The electrochemical test of the battery of Example 7 was carried out in the same manner as in Example 1.

[0210] 《Example 8》

[0211] The solid electrolyte composition of Example 8 was prepared in the same manner as in Example 6 except that the mass ratio of NCM-Nb to LYBC was changed to NCM-Nb:LYBC=90.9:9.1 and the solid content ratio was changed to 82.4% by mass. A battery of Example 8 was prepared using the solid electrolyte composition of Example 8 in the same manner as in Example 1. An electrochemical test of the battery of Example 8 was performed in the same manner as in Example 1.

[0212] 《Example 9》

[0213] In an environment with a dew point of -60°C or less, LYBC powder was mixed with parachlorotoluene and finely pulverized using a planetary ball mill to obtain a suspension. A conductive additive 1.5 times the mass of Example 1 was added to the suspension and mixed using a stirrer.

[0214] NCM-Nb and the suspension were put into a kneader so that the mass ratio of NCM-Nb to LYBC was NCM-Nb:LYBC=90.9:9.1, and p-chlorotoluene was added to adjust the solid content ratio to 82.8% by mass. Dry kneading was carried out under the same conditions as in Example 1 to obtain a solid electrolyte composition of Example 9.

[0215] Using the solid electrolyte composition of Example 9, a battery of Example 9 was produced in the same manner as in Example 1. Electrochemical tests of the battery of Example 9 were carried out in the same manner as in Example 1.

[0216] 《Example 10》

[0217] In an environment with a dew point of -60°C or less, LYBC powder is mixed with parachlorotoluene, and the LYBC powder is finely pulverized using a planetary ball mill to obtain a suspension. An appropriate amount of a conductive additive is added to the suspension, and the mixture is mixed using a stirrer.

[0218] NCM and the suspension were put into a planetary mixer (HIVIS MIX 2P-03 manufactured by PRIMIX Corporation) in a mass ratio of NCM to LYBC of NCM:LYBC=93.0:7.0, and parachlorotoluene was added to adjust the solid content ratio to 78.9% by mass. Then, dry-mixing was performed under the conditions of a rotation speed of 100 rpm, 1 hour, and an argon atmosphere with a dew point of -60°C. Thus, the solid electrolyte composition of Example 9 was obtained.

[0219] Using the solid electrolyte composition of Example 10, a battery of Example 10 was produced in the same manner as in Example 1. Electrochemical tests of the battery of Example 10 were carried out in the same manner as in Example 1.

[0220] Example 11

[0221] The solid electrolyte composition of Example 11 was prepared in the same manner as in Example 10 except that the mass ratio of NCM to LYBC was changed to NCM:LYBC=90.9:9.1 and the solid content ratio was changed to 83.5% by mass. The battery of Example 11 was prepared in the same manner as in Example 1 using the solid electrolyte composition of Example 11. The electrochemical test of the battery of Example 11 was carried out in the same manner as in Example 1.

[0222] Comparative Example 1

[0223] In an environment with a dew point of -60°C or less, LYBC powder is mixed with parachlorotoluene, and the LYBC powder is finely pulverized using a planetary ball mill to obtain a suspension. An appropriate amount of a conductive additive is added to the suspension, and the mixture is mixed using a stirrer.

[0224] NCM and the suspension were mixed so that the volume ratio of NCM to LYBC was NCM:LYBC=70:30, and the mixture was dispersed with a homogenizer. A binder and a solvent were added to the mixture, and each material was dispersed with a homogenizer to prepare a slurry of Comparative Example 1.

[0225] The slurry was applied to the current collector to form a coating film. The coating film was dried on a hot plate to prepare a positive electrode. The positive electrode was used to prepare a battery of Comparative Example 1 in the same manner as in Example 1. The electrochemical test of the battery of Comparative Example 1 was carried out in the same manner as in Example 1.

[0226] 《Example 12》

[0227] [Preparation of Solid Electrolyte Composition]

[0228] Li(NiCoAl)O2 (hereinafter referred to as NCA) was used as the positive electrode active material, and a coating layer of LiNbO3 was formed on the surface of NCA in the same manner as in Example 6. Hereinafter, NCA having a coating layer of LiNbO3 is referred to as "NCA-Nb".

[0229] In an environment with a dew point of -60°C or less, LPS powder and tetralin (THN) were mixed, and LPS was dispersed in tetralin using a homogenizer to obtain a suspension.

[0230] NCA-Nb and the suspension were put into a planetary mixer so that the mass ratio of NCA-Nb to LPS was NCA-Nb:LPS=91.3:8.7, tetralin was added to adjust the solid content ratio to 77.5% by mass, and dry kneading was carried out at a rotation speed of 100 rpm for 1 hour in an argon atmosphere with a dew point of -60°C. Thus, the solid electrolyte composition of Example 12 was obtained.

[0231] [Production of positive electrode]

[0232] In an argon glove box at a dew point below -60°C, a solid electrolyte composition was mixed with LPS to obtain a mixture. The ratio of NCA-Nb to LPS in the mixture was NCA-Nb:LYBC=70:30 by volume. The mixture was treated with a homogenizer to disperse NCA-Nb and LYBC. A binder, a solvent, and a conductive additive were added to the mixture and dispersed with a homogenizer to obtain a slurry.

[0233] The slurry was applied to a current collector to form a coating film, and the coating film was dried on a hot plate to prepare the positive electrode of Example 12.

[0234] It should be noted that in Example 12 and Comparative Example 2, the thickness of the coating film was adjusted in each of the Example and the Comparative Example so that the mass of the positive electrode active material layer after drying would be the same.

[0235] [Battery production]

[0236] Using the positive electrode of Example 12, a battery of Example 12 was manufactured in the same manner as Example 1.

[0237] [Electrochemical test]

[0238] The electrochemical test of the battery of Example 12 was carried out in the same manner as in Example 1. The results are shown in Table 1. In Table 2, the item "Discharge capacity" shows a relative value when the discharge capacity per unit area of ​​the battery of Comparative Example 2 is regarded as "100".

[0239] 《Comparative Example 2》

[0240] In an environment with a dew point of -60°C or less, LPS, tetralin and a binder were mixed, and each material was dispersed with a homogenizer to obtain a dispersion. NCA-Nb was mixed with the dispersion so that the volume ratio of NCA-Nb to LPS was NCA-Nb:LPS=70:30, and each material was dispersed with a homogenizer. A conductive additive was added, and the conductive additive was dispersed with a homogenizer to prepare a slurry.

[0241] The slurry was applied to a current collector to form a coating film, and the coating film was dried on a hot plate to prepare a positive electrode of Comparative Example 2.

[0242] Using the positive electrode of Comparative Example 2, a battery of Comparative Example 2 was produced in the same manner as in Example 1. An electrochemical test of the battery of Comparative Example 2 was carried out in the same manner as in Example 1.

[0243] [Table 1]

[0244]

[0245] [Table 2]

[0246]

[0247] Investigation

[0248] As shown in Tables 1 and 2, the battery of the embodiment showed a higher discharge capacity than the battery of the comparative example. The resistance of the battery decreased, the average discharge voltage and discharge capacity increased, and the energy per unit area increased. The reason for this is believed to be that a complex having a good interface between the active material and the solid electrolyte was formed.

[0249] The ease with which the interface between the active material and the solid electrolyte is formed when the dry-mixing step is not used varies depending on the type of material. Therefore, there is a difference in the degree of improvement over the comparative example between Examples 1 to 11 and Example 12.

[0250] In the dry-mixing process, the solid content ratio that determines the state and viscosity is important. The kneader has a large volume ratio of the blades relative to the volume in the chamber due to its structure. Therefore, when using a kneader, a strong shear force can be applied to the material. Therefore, the range of solid content ratios that can be applied to the kneader is wide, and on this basis, efficient dry-mixing can be achieved. However, the amount that can be processed by the kneader at one time is small.

[0251] On the other hand, the volume of the container for inputting materials is larger than the volume of the blades in the planetary mixer, so a large amount of materials can be dry-mixed at one time. However, it is difficult to apply shear force to the materials in the container, so the range of solid content ratio that can be applied to the planetary mixer is narrow.

[0252] Industrial Applicability

[0253] The technology of the present disclosure is useful, for example, for all-solid-state batteries.

Claims

1. A solid electrolyte composition comprising: Solvents, Active substances, and Solid electrolytes, The solid electrolyte composition is in powder or clay form, The active material is composited with the solid electrolyte.

2. The solid electrolyte composition according to claim 1, wherein The solid electrolyte composition is in the form of clay.

3. The solid electrolyte composition according to claim 1, wherein The solid electrolyte composition has a solid content ratio of 72 mass % or more and 88 mass % or less.

4. The solid electrolyte composition according to claim 1, wherein The solid electrolyte composition does not contain a binder.

5. A method for producing a solid electrolyte composition, comprising the following steps: The mixture including the solvent, the active material and the solid electrolyte is dry-mixed.

6. The method for producing a solid electrolyte composition according to claim 5, wherein: The mixture was clay-like.

7. The method for producing a solid electrolyte composition according to claim 5, wherein: The solid content ratio of the mixture is 72 mass % or more and 88 mass % or less.

8. The method for producing a solid electrolyte composition according to claim 5, wherein: The solid content ratio of the mixture is 77 mass % or more and 84 mass % or less.

9. The method for producing a solid electrolyte composition according to claim 5, wherein: The mixture contains no binder.

10. The method for producing a solid electrolyte composition according to claim 5, wherein: The solid electrolyte includes at least one selected from the group consisting of a sulfide solid electrolyte and a halide solid electrolyte.

11. A method for producing an electrode slurry, comprising the following steps: A solvent is added to the solid electrolyte composition according to claim 1.

12. A method for manufacturing an electrode, comprising the following steps: The solid electrolyte composition according to claim 1 is formed.

13. A method for manufacturing a battery, comprising the following steps: The solid electrolyte composition according to claim 1 is formed.

Citation Information

Patent Citations

  • All-solid-state battery

    JP2020053307A

  • Slurry composition for all-solid-state secondary cell, solid-electrolyte-containing layer, all-solid-state secondary cell, and method for manufacturing slurry composition for all-solid-state secondary cell

    WO2020241322A1